2009
DOI: 10.1111/j.1365-2052.2009.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of a wide‐spectrum chicken gene pool

Abstract: The genetic structure of 65 chicken populations was studied using 29 SSR loci. Six main clusters which corresponded to geographical origins and histories were identified: Brown Egg Layers, predominantly Broilers, native Chinese breeds or breeds with recent Asian origin, predominantly breeds of European derivation, a small cluster containing populations with No Common-History (NCH), and populations that had breeding history with White Leghorn. Another group of populations that shared their genome with several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…This study presents clear evidence that red JF and chickens have not been genetically isolated since domestication, as suggested elsewhere (35,74,115,116). Previous studies have found evidence for introgression of gray JF, which would have further altered the genetic variation present in the domestic chicken.…”
Section: The Origins Of High Diversity In Chickenssupporting
confidence: 84%
“…This study presents clear evidence that red JF and chickens have not been genetically isolated since domestication, as suggested elsewhere (35,74,115,116). Previous studies have found evidence for introgression of gray JF, which would have further altered the genetic variation present in the domestic chicken.…”
Section: The Origins Of High Diversity In Chickenssupporting
confidence: 84%
“…Since studied GTs were considered to be well suited for the established animal model concerning the required phylogenetic (Granevitze et al, 2009;Lyimo et al, 2014) and performance divergence (Lieboldt et al, 2015), the present study was conducted to examine interactions between these GTs and long-term graded Arg supply serving as nutritional-environmental stress on growth development and performance of diverse purebred layer lines.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known Bayesian clustering approach (Pritchard et al, 2000) detects the population structure based on the proposition of admixture between genetically divergent populations without a priori information of breeds (Allendorf et al, 2010;Tadano et al, 2011) and differs from traditional methods such as phylogenetic trees which assume genetic separation between breeds (Granevitze et al, 2009;Tixier-Boichard et al, 2009). The highest ΔK value was found at K=2 (data not shown) according to Evanno et al (2005).…”
Section: Breed Relationship and Population Clusteringmentioning
confidence: 99%